ANALISIS PENGARUH HEAT TREATMENT TERHADAP HASIL KEKERASAN BAJA SKD 61 PADA PISAU DIGESTER DI PT HINDOLI - agustina sintia (Motor Bakar : Jurnal Teknik Mesin, 2025)
This study aims to evaluate the effect of heat treatment (hardening) on the hardness of medium carbon steel with variations in temperature and holding time using an Electric Melting Furnace as the heating medium. The research began with a literature review and field survey, followed by the preparation of steel specimens. Hardening was performed at temperatures of 810°C, 860°C, and 890°C with holding times of 16 minutes, 22 minutes, and 28 minutes. Hardness testing was conducted using the Vickers hardness method to determine the changes in hardness for each treatment condition. The data from hardness tests were analyzed using Analysis of Variance (ANOVA) to assess the impact of temperature and holding time on steel hardness. The results revealed that the highest hardness was achieved at 860°C with a holding time of 22 minutes, yielding a hardness value of 749.68 HV. Microstructural analysis showed that the initial structure of the steel, consisting of ferrite and pearlite, was transformed into martensite after heat treatment. These findings provide insights into the relationship between temperature, holding time, and hardness in medium carbon steel, and offer valuable information for industrial applications requiring high hardness and wear resistance.